Islamic Modernization, Identity Politics and Religious Conservatism in Indonesia (Reflections on the Renewal of Nurcholish Madjid's Islamic Thought) - JAMAL, Syukron (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This research aims to trace the traces of the renewal of Nurcholish Madjid's Islamic thought, especially in the modernization of Islam, identity politics and Islamic religious conservatism.Methodology:In the context of this qualitative research, the researcher uses a discourse analysis approach. Researchers explore books and journal data sources relevant to the research topic through the library and research method.Findings:The research results show that for Cak Nur, reform must begin with two actions, one closely related to the other, namely breaking away from traditional values and seeking values oriented towards the future.Implication:In this connection, he put forward the idea of secularization as a liberation process. According to Cak Nur, this secularization process is essential, especially for the condition of Muslims who are no longer able to distinguish which values they think are Islamic, which are transcendent, and which are temporal; secularization is intended for worldly values that should be worldly and free Muslims from the tendency to make them worldly.